2021
DOI: 10.1245/s10434-021-10727-2
|View full text |Cite
|
Sign up to set email alerts
|

Merkel Cell Carcinoma: Changing Practice Patterns and Impact on Recurrence-Free and Overall Survival at a Single Institution and Nationally

Abstract: Background Merkel cell carcinoma (MCC) is an aggressive neuroendocrine carcinoma of the skin. Our report describes the evolution of management and characteristics associated with recurrence, disease-specific survival (DSS) and overall survival (OS) in the treatment of MCC. Methods A single institution retrospective review of MCC and SEER data to determine factors associated with RFS, DSS, and OS using a multivariable Cox regression on inverse-probability w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
1
1
0
Order By: Relevance
“…Although advanced age at diagnosis is known to be an independent prognostic factor associated with worse survival, different median or mean values for age at diagnosis have been reported in the literature (7,(19)(20)(21)(22). Results from the RCS analysis in the current study indicated that an age of 75 years was an appropriate inflection point for subsequent analysis (Figure 2), which was consistent with prior large sample size studies (23,24). In the multivariate analysis, advanced age at diagnosis was further proven to be an independent risk factor for the whole cohort as well as in the subgroup analysis.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Although advanced age at diagnosis is known to be an independent prognostic factor associated with worse survival, different median or mean values for age at diagnosis have been reported in the literature (7,(19)(20)(21)(22). Results from the RCS analysis in the current study indicated that an age of 75 years was an appropriate inflection point for subsequent analysis (Figure 2), which was consistent with prior large sample size studies (23,24). In the multivariate analysis, advanced age at diagnosis was further proven to be an independent risk factor for the whole cohort as well as in the subgroup analysis.…”
Section: Discussionsupporting
confidence: 87%
“…To date, accumulating evidence has shown encouraging results for immunotherapy in the treatment of MCC (23,31). In 2016, Kaufman et al conducted a single arm, phase II trial evaluating the efficiency of avelumab in CT-refractory metastatic MCC patients.…”
Section: Discussionmentioning
confidence: 99%